Carpal tunnel syndrome: between conservative treatment and those treated surgically after failed conservative treatment - Omar, B.M.I. (Faculty of Medicine, University of Malaya, 2005)
A retrospective study of 102 hands with carpal tunnel syndrome which were treated conservatively initially. Patients who were successfully treated with this method were then compared with those who had failed with this method and had to be treated with surgical decompression. This study found that it took a mean period of about 5.1 months of conservative treatment before deciding on surgery. Generally, the study shows a predominant involvement of the right hand and the female sex as full-time homemakers. Those who finally needed surgery had a longer duration of symptoms prior to consultation. Surgery brought a faster relief from both pain and numbness. It is recommended that conservative treatment be abandoned after a trial period of at least three to five months in order to encourage a speedier recovery.